2018
DOI: 10.1021/acs.iecr.8b02216
|View full text |Cite
|
Sign up to set email alerts
|

Demulsification of Light Malaysian Crude Oil Emulsions Using an Electric Field Method

Abstract: The creation of oil emulsions due to mechanical strength and natural surfactants during production is undesirable. The challenges associated with transporting and refining oil have led researchers to probe into practical demulsification methods. An in-depth understanding of crude oil rheology and operating conditions to treat emulsion is necessary. The main objective of the current study was to investigate the rheological behavior and demulsification rate of crude oil emulsions. The rheological behavior of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The authors concluded that crude oil demulsification using an alternating electric field was very effective for W/O emulsions. The rate of demulsification of W/O emulsions in direct current fields was reported by Mohammadian et al [143], who showed that the rate of water separation increased with the direct current fields. The authors concluded that the demulsification of crude oil emulsions was guided by the magnitude of the applied electric field and the type of electrode.…”
Section: Electrical Demulsificationmentioning
confidence: 54%
“…The authors concluded that crude oil demulsification using an alternating electric field was very effective for W/O emulsions. The rate of demulsification of W/O emulsions in direct current fields was reported by Mohammadian et al [143], who showed that the rate of water separation increased with the direct current fields. The authors concluded that the demulsification of crude oil emulsions was guided by the magnitude of the applied electric field and the type of electrode.…”
Section: Electrical Demulsificationmentioning
confidence: 54%
“…Adding a demulsifier resulted in a better outcome compared to the addition of demulsifiers after emulsification. Moreover, a study was carried out to demulsified light Malaysian crude oil emulsion by utilizing electrical technique; there was undesirable production of crude oil emulsion through natural surfactants and mechanical strength [41]. Nevertheless, the problems emanating from refining oil and its transportation have propelled the use of practical demulsification techniques.…”
Section: Electrical Methodsmentioning
confidence: 99%
“…The solutions were added to an autoclave and deoxygenated by purging with nitrogen gas for two hours before the beginning of each experiment. All experiments were conducted at 60°C and pH 3.0 ± 0.5 to simulate the crude oil conditions in Southeast Asia especially around Malaysian region (30°C–90°C and pH 2–6) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%